Cardiac adaptation to endurance exercise training: Differential impact of swimming and running - Martinez, V.; Sanz de la Garza, M.; Grazioli, G.; Roca, E.; Brotons, D.; Sitges, M. (European Journal of Sport Science, 2021)
Objectives: High-intensity training has been associated with bi-ventricular and bi-atrial remodelling and a potentially increased risk of arrhythmias. Most of the evidence is based on endurance disciplines mainly involving the lower part of the body, while few data is available on upper body disciplines. The purpose of this study was to compare chronic cardiac remodelling induced by running and swimming as well as the acute response of ventricular and atrial performance after an upper-body and a lower-body endurance race. Methods: Standard and speckle tracking echocardiographic assessment of left ventricle, right ventricle and both atria was performed at baseline and immediately after a 9.5 km open-water swimming race in 26 healthy men and before and after a 35 km-trail-running race in 21 male runners. Results: No significant differences were observed in baseline ventricular dimensions. However, both right ventricular and atrial systolic deformation were greater in runners. This group also showed slightly larger atrial volumes as compared to swimmers. After the race, right ventricular dilatation was observed in both groups, but only runners showed a decrease in right ventricular deformation and a decrease in atrial volumes and deformation. Significant increases in atrial deformation without reduction in atrial volumes were observed only in swimmers after the race. Conclusions: Right ventricular and atrial remodelling is different depending on the endurance training discipline. Long-distance running races induce a greater impairment in right ventricular performance and atrial function compared to endurance swimming competitions.